PELATIHAN TEKNIK SITASI MENGGUNAKAN APLIKASI MENDELEY SEBAGAI DIREKTORI DAFTAR RUJUKAN KARYA ILMIAH BAGI MAHASISWA PGSD UNIVERSITAS MATARAM - Arif Widodo; Vivi Rachmatul Hidayati; Dyah Indraswati; Umar; Lalu Hamdian Affandi (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2023)
Writing scientific articles is an obligation for several people, one of which is a college student. College students as prospective teachers must be equipped with the ability to formulate problems to implement the scientific method by publishing their research. In writing scientific papers, there are rules that must be obeyed, one of which is citation and compiling a list of references. The problem obtained is that students have difficulty in carrying out these stages. The solution that can be done is to use the Mendeley application. The target of this activity is the 6th semester of PGSD University of Mataram students who have or are currently taking a scientific paper writing course. The results showed that there was a significant increase in the pre-test to post-test average. This shows that the training provided has had a good impact in terms of knowledge and insight regarding citations and preparation of reference lists with the Mendeley application.